Short term increase in risk of breast cancer after full term pregnancy. Issue 6656 (29th October 1988) - Bruzzi, P.; Negri, E.; La Vecchia, C.; Decarli, A.; Palli, D.; Parazzini, F.; Del Turco, M. R.
Abstract : To determine whether there is a short term increase in the risk of breast cancer after a full term birth data from two hospital based, case-control studies in Italy were pooled. Analysis was restricted to women aged under 50 with two or more children (573 women with cancer and 570 controls). A relative risk for breast cancer of 2.66 was seen in women who had given birth during the three years preceding the interview compared with women whose last birth had occurred 10 or more years before, after adjustment for age, age at first birth, and parity. The relative risk slowly decreased for women who had last given birth three to 10 years before. Multivariate analyses confirmed the protective effect of an early age at first birth and the age dependent effect of parity on the risk of breast cancer–that is, a direct relation below age 40 and an inverse one in older women. These data provide epidemiological evidence that a full term birth is followed by a transient increase in the risk of breast cancer, which for some time contrasts with and overcomes the long term protection of pregnancy at an early age. They therefore confirm predictions from animal studies and theoretical models that pregnancy prevents the early stages of breast carcinogenesis but promotes the late stages of the process.